2019
DOI: 10.3389/fcimb.2019.00147
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Protection Against Four Serotypes of Dengue Virus in Mice Conferred by a Zika DNA Vaccine

Abstract: Both Zika virus (ZIKV) and four serotypes of dengue virus (DENV1–4) are antigenically related mosquito-borne flaviviruses that co-circulate in overlapping geographic distributions. The considerable amino acid sequence homology and structural similarities between ZIKV and DENV1–4 may be responsible for the complicated immunological cross-reactivity observed for these viruses. Thus, a successful Zika vaccine needs to not only confer protection from ZIKV infection but must also be safe during secondary exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Therefore, it is still unclear whether systemic thrombo-inflammatory responses might converge with endothelial injury caused by DENV. Nevertheless, intracerebral inoculation of mice is a plausible in vivo model that allows virus replication and measurable clinical parameters [ 29 , 30 ], and have been standardly used in antiviral and vaccine preclinical trials [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is still unclear whether systemic thrombo-inflammatory responses might converge with endothelial injury caused by DENV. Nevertheless, intracerebral inoculation of mice is a plausible in vivo model that allows virus replication and measurable clinical parameters [ 29 , 30 ], and have been standardly used in antiviral and vaccine preclinical trials [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several studies have indicated complex interactions between DENV and ZIKV immunity (Breitbach et al 2019 ; Fowler et al 2018 ; Pantoja et al 2017 ; Slon-Campos et al 2019 ; Wang et al 2019a ; Zimmerman et al 2018 ). Clinical data suggest that pre-existing DENV immunity is partially protective against symptomatic ZIKV infection and against congenital ZIKV syndrome (Gordon et al 2019 ; Pedroso et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several studies have indicated complex interactions between DENV and ZIKV immunity (7-12). Clinical data suggest that pre-existing DENV immunity is partially protective against symptomatic ZIKV infection and against congenital ZIKV syndrome (13, 14).…”
Section: Introductionmentioning
confidence: 99%